(untitled) (REMUNOM, 2026)
The transition to the post-digital era has intensified the demand for spaces that support creative and collaborative intellectual processes. This study systematizes design guidelines for architecture oriented toward the Creative Economy, taking as its object the authorial prototype of the School of Digital Technologies. The method, with an applied qualitative approach, is organized into: bibliographic review, analysis of regional architectural repertoire, target audience characterization, and topographic survey. The results reveal the following guidelines: (a) needs program derived from primary data, including expert interviews and CNAE mapping; (b) environmental comfort strategies; (c) spatial flexibility grounded in the post-digital era, with versatile furniture; (d) biophilic design guided by mental health data of the target audience. The results suggest that social, economic, and digital inclusion, combined with the design process, are conditions that, under traceable methodologies, reinforce each other and have replication potential.